A case report of an endoscopic approach to life‐threatening cecal variceal hemorrhage. Issue 4 (7th April 2022) - MacFarlane, Kirsty E; Fischer, Nicholas J
Abstract: Cecal varices are a rare cause of gastrointestinal bleeding in patients with cirrhosis. We describe a 29‐year‐old man with decompensated alcoholic cirrhosis who developed gastrointestinal bleeding in the hospital. A computed tomography mesenteric angiogram showed bleeding cecal varices, which were successfully treated by glue injection therapy at colonoscopy. The procedure appeared to be complicated by bacteremia due to Escherichia coli . Abstract : Cecal varices have a high mortality rate likely due to being amongst the rarest complications of portosystemic hypertension. This is the case report of a 29‐year‐old man who developed life threatening hemorrhaging cecal varices but was treated successfully and survived, bringing to the academic world some potential treatment options and adding to the paucity of literature.